I templi del Fayyum in epoca tolemaico-romana tra fonti scritte e contesti archeologici : per una classificazione degli edifici sacri nell'Egitto tolemaico e romano - Rossetti, Ilaria, (Archaeopress Egyptology ;, 2020)
During the Ptolemaic period, Egyptian temples were divided into three ranks: first, second and third class. There was no trace of this classification of sacred buildings in the papyri of the Roman period when only the most important temples were classified by the epithet logima hiera. This work aims to understand the rules according to which Egyptian sacred buildings were classified and how these first, second and third-class temples were planned and arranged. To do this, an integrated analysis of different kinds of sources was carried out: all the Graeco-Roman papyri and the inscriptions, which contain rank epithets, were examined and different archaeological data about the temples of the Fayyum region were investigated. Based on these sources, it was possible to put forward different hypotheses on the administration and architectural aspects of these sacred buildings.